Pengaruh Motivasi Dan Lingkungan Kerja TerhadapKinerja Karyawan(Studi Empiris Pada PT MISAJA MITRA PATI) - Cahyani, Sinta Moekti Dwi; , Anton Agus Setyawan, SE., M.Si (2017)
This study aims to analyze the influence of motivation, work environment on employee performance PT Misaja Mitra Pati individually and together. This research method using research type of quantitative approach. This study uses the population is employees of PT Misaja Mitra Pati with the number of 425 people using a sample sample of 100 people. Sampling using random sampling method. Data analysis method used is validity test, reliability test, classical assumption test and multiple linear regression analysis test with t test, F test, and coefficient of determination (R2). The result of t test analysis can be got motivation, work environment influence to employee performance of PT Misaja Mitra Pati individually whereas F test result can be got motivation, work environment influence to employee performance PT Misaja Mitra Pati together.